2013
DOI: 10.1044/1059-0889(2012/12-0067)
|View full text |Cite
|
Sign up to set email alerts
|

Examining Speech Perception in Noise and Cognitive Functions in the Elderly

Abstract: The results support the assumption that WM plays an important role for speech understanding and that it might have impact on results obtained using speech audiometry. Thus, an individual's WM capacity should be considered with aural diagnosis and rehabilitation. The VLMT proved to be a clinically applicable test for WM. Further cognitive functions important with speech understanding are currently being investigated within the SAKoLA (Sprachaudiometrie und kognitive Leistungen im Alter [Speech Audiometry and Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 6 publications
5
20
2
2
Order By: Relevance
“…Indeed, this is not consistent with most previous findings suggesting that WM abilities are involved and partially explain SiS perception performance [2729]. The lack of a correlation between WM capacity and semantic priming in our study might be explained by the selection of the digit span task of the WAIS to evaluate WM abilities.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Indeed, this is not consistent with most previous findings suggesting that WM abilities are involved and partially explain SiS perception performance [2729]. The lack of a correlation between WM capacity and semantic priming in our study might be explained by the selection of the digit span task of the WAIS to evaluate WM abilities.…”
Section: Discussioncontrasting
confidence: 99%
“…Among cognitive abilities supporting SiS processing and comprehension, it is suggested that working memory (WM)—one of the executive function (EF) abilities ([1719], see also [2022])—is a key component of language comprehension [2326]. Consistent with this assumption, studies have suggested that a decline in WM capacity in older adults is related to a decline in SiS comprehension [27]. Furthermore, in hearing aid users and hearing impaired people, it has been reported that better WM scores are related to better speech-in-noise performance [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have suggested that cognitive ability should be evaluated in individuals seeking hearing rehabilitation (Edwards, 2007; Meister et al, 2013; Sirow & Souza, 2013). For example, Smith (2012) recently proposed that memory and processing tasks could be incorporated within speech-recognition measures.…”
Section: Discussionmentioning
confidence: 99%
“…The global test in itself is an automated version of the synthetic sentence test, termed the synthetic sentences identification test (SSI) (King-Smith and Rose, 1997; Kaernbach, 2001;Buss et al, 2009;MacPherson and Akeroyd, 2014;Kollmeier, 2015). The novelty and the strength of the test are the speech noise material, with features inspired by ICRA noise, and its simplicity in performing adaptive exams (Dreschler et al, 2001;Wagener et al, 2006;Meister et al, 2013;Akeroyd et al, 2015). Reviewing reference ranges and standard deviations for the Italian language of the OLSA test, published by Puglisi et al (2015), allowed determination of different levels to identify at-risk patients.…”
Section: Audiological Assessmentmentioning
confidence: 99%